HUBUNGAN ANTARA KEPRIBADIAN (PERSONALITY) DENGAN SARANA SANITASI LINGKUNGAN (Survey pada Masyarakat di Kelurahan Slipi, Kecamatan Palmerah, Jakarta Barat) - Fu'adiyah, Rohma Isti; Sapta Dewi, Yusriani (JURNAL TECHLINK, 2023)
Environmental sanitation greatly affects human health if an environment has good sanitation, the health status will increase and vice versa if an environment has poor sanitation, it will cause illness. The purpose of this study was to determine the relationship between personality (Personality) and environmental sanitation facilities, with respondents as many as 97 people of RW 02 slipi. From this survey, it is found that there is a positive and significant relationship between personality and means of environmental sanitation. Based on these findings, it can be concluded, if environmental sanitation facilities are improved, then personality needs to be improved even better.